Days alive and out of hospital in patients with wild type transthyretin amyloidosis: cohort study - Mariana Vaena; María Adela Aguirre; Teo Epstein; Agustín Schalum; Facundo Ezequiel Hilbert; María Lourdes Posadas-Martínez; Marcelina Carretero (Scientific Reports)
Abstract While overall survival has been extensively studied in amyloidosis, less attention has been given to patient-centered measures that integrate morbidity and mortality. Days Alive and Out of Hospital (DAOH) is an emerging metric that captures both aspects and has potential utility in the evaluation of disease impact.To describe DAOH in patients with wild-type transthyretin amyloidosis (ATTRwt) and explore factors associated with DAOH.Retrospective cohort study used the Institutional Registry of Amyloidosis database of the Hospital Italiano de Buenos Aires (2015–2023). All patients with ATTRwt amyloidosis enrolled in the registry and affiliated with the health maintenance organization of the hospital were included. DAOH were estimated at 1, 3 and 5 years. Associations between DAOH and risk factors were evaluated.61 cases were included. The median age was 83 years, and 89% were male. Median (IQR) DAOH were 365 (353–365), 998 (553–1094) and 1314 (740–1769) days for 1, 3, and 5 years, respectively. Atrial fibrillation was associated with lower DAOH.DAOH is a simple, reproducible metric. Our findings highlight the importance of considering morbidity, not just mortality, in patients with ATTRwt amyloidosis.